Anne Clifford's autobiographical writing, 1590-1676 - Pembroke, Anne Clifford Herbert, Countess of, 1590-1676 (Book collections on Project MUSE., 2018)
Anne Clifford describes the dramatic and tragic events of her life in the seventeenth century. Of how she danced in the masques of Inigo Jones, experienced both joy and abuse in her two marriages, lost and gained an inheritance, and successfully defended her rights against kings and armies. All told in rich detail amidst the backdrop of daily life.